Environmental accounting commitment and propaganda - Freedman, Martin; Jaggi, Bikki (Emerald, 2006)
In the two years since the publication of the last volume of this series, the planet has witnessed some devastating environmental events some of which can be attributed to human causes. However, we have also seen the world uniting (except mainly for the United States and Australia) to reduce greenhouse gases and hopefully slowdown global warming. Recognizing that sustainable development is a way that can lead to well being of the society in the long run, most of the world has therefore agreed to ratify the Kyoto Protocol. There is hope that the USA and other industrialized countries will ratify the Protocol and all countries including China and India, which are exempt from emission cuts, will make efforts to reduce pollution emissions beyond the limit set by the Protocol. Economic growth in China and India is resulting in a rapid increase in the greenhouse gas emissions in those countries.-It is especially important that plants in India and China use newer pollution technologies in generating electricity to meet their energy needs. Their continued participation in the dialogue is important to control pollution emissions beyond the Kyoto Protocol. Environmental issues are multi-faceted and they are being debated in several disciplines. These issues may be technical, legal, economical, measurement, managerial, or ethical in nature, and different disciplines focus on the issues of interest to them. Accounting is primarily concerned with measurement of pollution-related performance and cost, and reporting of this information to stakeholders. Consistent with the goals of Sarbanes-Oxley Act, it is important that accounting regains its lost credibility and provides reliable pollution-related information to the stakeholders so that they evaluate their risk properly.-This volume contains papers which deal with some of the important issues related to pollution information and should be of interest to investors, management, regulators and other individuals interested in environmental accounting. Several papers contained in this volume deal with disclosure of environmental information. Some papers examine what motivates environmental disclosures, whereas other examine whether environmental reporting reflects any real commitment or it is merely a propaganda ploy. While some firms may be genuinely interested in reporting their environmental performance correctly, others may use it as a tool to look good. Another paper in this issue shows that an alignment of management commitment, strategic planning and proactive managerial actions result in better environmental performance and this leads to better return on investment.-Though there is no uniform format for reporting environmental information, the last paper in this issue provides discussion on integrating the living systems theory with the accounting disclosure model. In brief, this issue contains several interesting articles dealing with different aspects of environmental disclosures. It addresses the Kyoto Protocol on an international level, discusses how an accountant measures pollution-related performance and cost, and investigates the motive behind disclosure of environmental information.
Keywords: Environmental auditing.; elektronické knihy; electronic books